Prove that,
Answers
Answered by
2
SOLUTION :-
Answer
Find the following limit:
lim_(x->0) (x-log(x+1))/(1-cos(x))
Applying l'Hôpital's rule, we get that
lim_(x->0) (x-log(x+1))/(1-cos(x)) | = | lim_(x->0) ( d/( dx)(x-log(x+1)))/( d/( dx)(1-cos(x)))
| = | lim_(x->0) (1-1/(x+1))/(sin(x))
| = | lim_(x->0) x/((x+1) sin(x))
lim_(x->0) x/(sin(x) (x+1))
By the product rule,
lim_(x->0) x/((x+1) sin(x)) = (lim_(x->0) x/(sin(x)))/(lim_(x->0) (x+1)):
1/(lim_(x->0) (x+1)) lim_(x->0) x/(sin(x))
x+1 is a polynomial and thus everywhere continuous, so
lim_(x->0) (x+1) = 1+0 = 1:
(lim_(x->0) x/(sin(x)))/(1)
Applying l'Hôpital's rule, we get that
lim_(x->0) x/(sin(x)) = lim_(x->0) (( dx)/( dx))/( d/( dx) sin(x)) = lim_(x->0) 1/(cos(x))
lim_(x->0) 1/(cos(x))
Applying the quotient rule, write lim_(x->0) 1/(cos(x)) as (lim_(x->0) 1)/(lim_(x->0) cos(x)):
1/(lim_(x->0) cos(x))
Since cosine is a continuous function,
lim_(x->0) cos(x) = cos(0) = 1:
1/1
1/1 = 1=R.H.S
Answer
Find the following limit:
lim_(x->0) (x-log(x+1))/(1-cos(x))
Applying l'Hôpital's rule, we get that
lim_(x->0) (x-log(x+1))/(1-cos(x)) | = | lim_(x->0) ( d/( dx)(x-log(x+1)))/( d/( dx)(1-cos(x)))
| = | lim_(x->0) (1-1/(x+1))/(sin(x))
| = | lim_(x->0) x/((x+1) sin(x))
lim_(x->0) x/(sin(x) (x+1))
By the product rule,
lim_(x->0) x/((x+1) sin(x)) = (lim_(x->0) x/(sin(x)))/(lim_(x->0) (x+1)):
1/(lim_(x->0) (x+1)) lim_(x->0) x/(sin(x))
x+1 is a polynomial and thus everywhere continuous, so
lim_(x->0) (x+1) = 1+0 = 1:
(lim_(x->0) x/(sin(x)))/(1)
Applying l'Hôpital's rule, we get that
lim_(x->0) x/(sin(x)) = lim_(x->0) (( dx)/( dx))/( d/( dx) sin(x)) = lim_(x->0) 1/(cos(x))
lim_(x->0) 1/(cos(x))
Applying the quotient rule, write lim_(x->0) 1/(cos(x)) as (lim_(x->0) 1)/(lim_(x->0) cos(x)):
1/(lim_(x->0) cos(x))
Since cosine is a continuous function,
lim_(x->0) cos(x) = cos(0) = 1:
1/1
1/1 = 1=R.H.S
Swarup1998:
Do the solution in notebook instead :(
Answered by
3
Answer: 1
Step-by-step explanation:
Given,
![\lim_{x\to0}\frac{x-\log{(1+x)}}{1-\cos x}\\\;\\\text{Putting}\;\cos x=1-2\sin^2\frac{x}{2}\\\;\\\lim_{x\to0}\frac{x-\log(1+x)}{1-1+2\sin^2\frac{x}{2}}\\\;\\=\lim_{x\to0}\frac{x-\log(1+x)}{2\sin^2\frac{x}{2}}\\\;\\=4\lim_{x\to0}\frac{x-[x-\frac{x^2}{2}+\frac{x^3}{3}-\frac{x^4}{4}+.........]}{2x^2\frac{\sin^2\frac{x}{2}}{\frac{x^2}{4}}}\\\;\\ \lim_{x\to0}\frac{x-\log{(1+x)}}{1-\cos x}\\\;\\\text{Putting}\;\cos x=1-2\sin^2\frac{x}{2}\\\;\\\lim_{x\to0}\frac{x-\log(1+x)}{1-1+2\sin^2\frac{x}{2}}\\\;\\=\lim_{x\to0}\frac{x-\log(1+x)}{2\sin^2\frac{x}{2}}\\\;\\=4\lim_{x\to0}\frac{x-[x-\frac{x^2}{2}+\frac{x^3}{3}-\frac{x^4}{4}+.........]}{2x^2\frac{\sin^2\frac{x}{2}}{\frac{x^2}{4}}}\\\;\\](https://tex.z-dn.net/?f=%5Clim_%7Bx%5Cto0%7D%5Cfrac%7Bx-%5Clog%7B%281%2Bx%29%7D%7D%7B1-%5Ccos+x%7D%5C%5C%5C%3B%5C%5C%5Ctext%7BPutting%7D%5C%3B%5Ccos+x%3D1-2%5Csin%5E2%5Cfrac%7Bx%7D%7B2%7D%5C%5C%5C%3B%5C%5C%5Clim_%7Bx%5Cto0%7D%5Cfrac%7Bx-%5Clog%281%2Bx%29%7D%7B1-1%2B2%5Csin%5E2%5Cfrac%7Bx%7D%7B2%7D%7D%5C%5C%5C%3B%5C%5C%3D%5Clim_%7Bx%5Cto0%7D%5Cfrac%7Bx-%5Clog%281%2Bx%29%7D%7B2%5Csin%5E2%5Cfrac%7Bx%7D%7B2%7D%7D%5C%5C%5C%3B%5C%5C%3D4%5Clim_%7Bx%5Cto0%7D%5Cfrac%7Bx-%5Bx-%5Cfrac%7Bx%5E2%7D%7B2%7D%2B%5Cfrac%7Bx%5E3%7D%7B3%7D-%5Cfrac%7Bx%5E4%7D%7B4%7D%2B.........%5D%7D%7B2x%5E2%5Cfrac%7B%5Csin%5E2%5Cfrac%7Bx%7D%7B2%7D%7D%7B%5Cfrac%7Bx%5E2%7D%7B4%7D%7D%7D%5C%5C%5C%3B%5C%5C)
![=2\lim_{x\to0}\frac{\frac{x^2}{2}-\frac{x^3}{3}+\frac{x^4}{4}........}{x^2}.\lim_{x\to0}\frac{1}{\frac{\sin\frac{x}{2}}{\frac{x}{2}}.\frac{\sin\frac{x}{2}}{\frac{x}{2}}}\\\;\\=2\lim_{x\to0}\frac{\frac{1}{2}-\frac{x}{3}+\frac{x^2}{4}....}{1}.1\\\;\\=2(\frac{1}{2}-0+0.....)\\\;\\=1 =2\lim_{x\to0}\frac{\frac{x^2}{2}-\frac{x^3}{3}+\frac{x^4}{4}........}{x^2}.\lim_{x\to0}\frac{1}{\frac{\sin\frac{x}{2}}{\frac{x}{2}}.\frac{\sin\frac{x}{2}}{\frac{x}{2}}}\\\;\\=2\lim_{x\to0}\frac{\frac{1}{2}-\frac{x}{3}+\frac{x^2}{4}....}{1}.1\\\;\\=2(\frac{1}{2}-0+0.....)\\\;\\=1](https://tex.z-dn.net/?f=%3D2%5Clim_%7Bx%5Cto0%7D%5Cfrac%7B%5Cfrac%7Bx%5E2%7D%7B2%7D-%5Cfrac%7Bx%5E3%7D%7B3%7D%2B%5Cfrac%7Bx%5E4%7D%7B4%7D........%7D%7Bx%5E2%7D.%5Clim_%7Bx%5Cto0%7D%5Cfrac%7B1%7D%7B%5Cfrac%7B%5Csin%5Cfrac%7Bx%7D%7B2%7D%7D%7B%5Cfrac%7Bx%7D%7B2%7D%7D.%5Cfrac%7B%5Csin%5Cfrac%7Bx%7D%7B2%7D%7D%7B%5Cfrac%7Bx%7D%7B2%7D%7D%7D%5C%5C%5C%3B%5C%5C%3D2%5Clim_%7Bx%5Cto0%7D%5Cfrac%7B%5Cfrac%7B1%7D%7B2%7D-%5Cfrac%7Bx%7D%7B3%7D%2B%5Cfrac%7Bx%5E2%7D%7B4%7D....%7D%7B1%7D.1%5C%5C%5C%3B%5C%5C%3D2%28%5Cfrac%7B1%7D%7B2%7D-0%2B0.....%29%5C%5C%5C%3B%5C%5C%3D1)
Step-by-step explanation:
Given,
Similar questions